Development of a Highly Sensitive Electrochemical Sensing Platform for the Trace Level Detection of Lead Ions. Issue 9 (22nd April 2019) - Shah, Afzal; Zahid, Anum; Khan, Amjad; Iftikhar, Faiza Jan; Nisar, Jan; Fernandez, Carlos; Akhter, Mohammad Salim; Almutawah, Abdulla Ali; Kraatz, Heinz-Bernhard
Abstract : Herein we report for the first time a highly sensitive electrochemical platform for the trace level detection of Pb (ӏӏ) using glassy carbon electrode modified with 1-dodecanoyl-3-phenylthiourea (DPT). The performance of the designed sensor was tested by electrochemical impedance spectroscopy, chronocoulometry, cyclic voltammetry and Square Wave Anodic Stripping Voltammetry (SWASV). The DPT was found to play an efficient role in enhancing the sensing response of the electrode for the detection of lead ions in aqueous samples. A number of experimental conditions such as deposition potential, accumulation time, surfactant concentration, pH, number of scans and supporting electrolytes were examined to optimize conditions for getting intense signal of the target analyte. Linear calibration curve was obtained using SWAS voltammetric data obtained under optimized conditions. The limit of detection with a value of 0.695 μg/L suggests that the designed sensor can sense lead ions even below the permissible concentration level (10 μg/L) recommended by the World Health Organization and Environmental Protection Agency of USA. The designed sensor demonstrated sensitivity, selectivity and stability for the targeted analyte. Percentage recoveries from real water samples with standard deviations of less than 2% suggested precision of the proposed method. Moreover, computational findings supported the experimental outcomes.